Assessment of awake i-gel™ insertion for fiberoptic-guided intubation in patients with predicted difficult airway: A prospective, observational study - Julian Arevalo Ludena; Jose Juan Arcas Bellas; Rafael Alvarez Rementeria; Luis Enrique Muñoz Alameda (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Orotracheal intubation (OTI) with fiberoptic bronchoscope (FOB) in spontaneous ventilation is one of the main techniques for patients with predicted difficult airway. Latest generation supraglottic airway devices have been designed to allow OTI through them. We assessed the safety and effectiveness of FOB-guided OTI through i-gel™ device which was inserted in spontaneously breathing patients with predicted difficult airway. Material and Methods: Eighty-five patients with difficult airway predictors were included. The i-gel was inserted under oropharyngeal local anaesthesia and sedation. After checking the adequate ventilation through the i-gel with capnography curve, general anaesthesia was induced in order to introduce the endotracheal tube guided by FOB. We recorded the i-gel insertion time (tgel), intubation time (tint), O2 saturation in pulse oximetry (SpO2) at different times: basal (t0), after 3 min of preoxygenation with a face mask at 100% FiO2 (t1), after i-gel mask insertion (t2) and after intubation (t3). Adverse events during the procedure were also recorded. Results: All patients were successfully intubated. SpO2 values were: 96.9 ± 1.2 (t0), 99.0 ± 0.9 (t1), 96.2 ± 2.4 (t2), 96.0 ± 2.5 (t3). tgel and tint were 38.0 ± 7.8 s and 36.5 ± 5.6 s, respectively. No serious adverse events were recorded and no patient suffered airway trauma. Conclusion: I-gel insertion in spontaneous ventilation secures the airway before achieving fiberoptic intubation without the occurrence of adverse events. More studies might be necessary in order to confirm the results presented, but we consider that the technique described is a safe and effective alternative to classic OTI with FOB in spontaneously breathing patients with predicted difficult airway.